Bone and joint diseases in the elderly - Hayashi, Yasufumi (Nihon Rōnen Igakkai zasshi, 2002)
As a current attention of the medical treatment has been paid to improve guality of the life rather than to save the life of the patient, so the treatment of bone and joint diseases, which are not ordinarily fatal and deteriorate quality of the life of the patient, would become important in the aged society of 21 century. In a strategy to improve the quality of life in the patient with osteoarthritis, disease modifying anti-osteothritis drugs are investigated for primary prevention and complete recovery of osteoarthritis. In osteoporosis, a characteristic bone disease of the aged, aims of the treatment have been changed from freeing of pain in the nineteen sixties, increase of bone mass in the nineteen eighties and reduction of the fracture rate in the nineteen nineties to improve of quality of the life through decrease of pain and fracture in 21 century, In conclusion, current management for bone and joint diseases in the elderly is finally designed to enjoy a healthy life of long span by medical intervention.